The Burden of COPD in China and Its Provinces: Findings From the Global Burden of Disease Study 2019 - Peng Yin; Jiayuan Wu; Lijun Wang; Chaole Luo; Lihuan Ouyang; Xiantong Tang; Jiangmei Liu; Yunning Liu; Jinlei Qi; Maigeng Zhou; Tianwen Lai (Frontiers Media S.A., 2022)
In China, chronic obstructive pulmonary disease (COPD) was accounted for a quarter of the global COPD population and has become a large economic burden. However, the comprehensive picture of the COPD burden, which could inform health policy, is not readily available for all of the provinces of China. Here, we aimed to describe the burden of COPD in China, providing an up-to-date and comprehensive analysis at the national and provincial levels, and time trends from 1990 to 2019. Following the methodology framework and general analytical strategies used in the GBD 2019, we analyzed the incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years with life lost (YLLs) attributable to COPD across China and the corresponding time trends from 1990 to 2019, stratified by age and province. In order to quantify the secular trends of the burden of COPD, the estimated annual percentage changes were calculated by the linear regression model of age-standardized rates (ASRs) and calendar years. We also presented the contribution of risk factors to COPD-related mortality and DALYs. The association between COPD burden and socio-demographic index (SDI) were also evaluated. From 1990 to 2019, the incidence and prevalence numbers of COPD increased by 61.2 and 67.8%, respectively, whereas the number of deaths and DALYs owing to COPD decreased. The ASRs of COPD burden, including incidence, prevalence, mortality, DALYs, YLDs, and YLLs continuously decreased from 1990 to 2019. The crude rates of COPD burden dramatically increased with age and reached a peak in the older than 95 years age group. In 2019, the leading risk factor for COPD mortality and DALYs was tobacco use in the whole population, but ambient particulate matter pollution was the most significant risk factor in females. At the provincial level, the ASRs of COPD burden was significantly associated with the SDIs, with the highest ASRs in the western provinces with low SDIs. Collectively, our study indicated that COPD remains an important public health problem in China. Geographically targeted considerations should be developed to enhance COPD health and reduce the COPD burden throughout China and in specific provinces.